Pattern of Eosinophil and Neutrophil/ Lymphocyte Ratio in Different Stages of Chronic Kidney Disease. (Bangladesh Medical Journal, 2024)
Various expensive interventions are used to diagnosis the different stages of chronic kidney disease (CKD). This research is aimed to determine the pattern of eosinophil and neutrophil/ lymphocyte ratio in different stages of CKD. Data was collected in January 2023 from the patients of CKD and from their files of reports. Permission was taken from the patients. The individuals were from civil hospital Karachi and they were the patients of CKD. Sample size was 200. There was irregular pattern of eosinophil and neutrophil/lymphocyte ratio in different stages of CKD. The eosinophil count and neutrophil/ lymphocyte ratio were higher in higher stages of CKD. The eosinophil and neutrophil/ lymphocyte ratio were higher in higher stages of CKD and the pattern was irregular. Study finds that eosinophil and neutrophil/ lymphocyte ratio were higher and the pattern was irregular in higher stages of CKD.Bangladesh Med J. 2023 Jan; 52(1): 24-29